Detection of dengue virus in individual Aedes aegypti mosquitoes in Delhi, India - Kumar Vikram; B N Nagpal; Veena Pande; Aruna Srivastava; Rekha Saxena; Himmat Singh; Anushrita; Sanjeev K Gupta; N R Tuli; N K Yadav; Telle Olivier; Paul Richard; et al. (Journal of Vector Borne Diseases, 2015)
Background & objectives: Delhi, the capital city of India, has so far witnessed several outbreaks of dengue fever since 1967 (last one reported in 2013). Improved virological and entomological surveillance are the only tools that can help in prevention of dengue as well as in the development of dengue control programmes. The aim of the study was to conduct a prospective field study to detect dengue virus in adult Aedes aegypti mosquitoes collected from various localities represented by different socioeconomic groups in Delhi. Methods: The study areas were selected and categorized into high, medium and low income groups on the basis of socioeconomical characteristics of the resident population, where dengue cases were reported during the past three years by MCD. Dengue viral infection was detected in the head squash of each adult mosquito by immunofluorescent assay (IFA) employing monoclonal antibodies against dengue virus (DENV). A total of 2408 females and 1206 males of Ae. aegypti were collected and tested by IFA. Results: Out of 2408 Ae. aegypti females, 14 were found positive, with minimum infection rate (MIR) of 5.8 per 1000 mosquitoes. Among the 18 study areas, 11 localities were found positive for dengue virus infection. Low income group (LIG) areas showed highest mosquito infectivity (9.8), followed by medium income group (MIG), i.e. 6.2; while least was observed in high income group (HIG), i.e. 1.3. No vertical transmission of dengue virus could be detected in 1206 Ae. aegypti males collected. Interpretation & conclusion: The study concludes that there was high MIR in the identified localities of low and medium income groups. Estimation of MIR in a female Aedes mosquito in the existing arsenals for dengue surveillance would be an added advantage for early warning of dengue outbreak. The presence of infected mosquitoes in identified localities of Delhi was alarming and require rigorous vector surveillance so that the severe outbreaks can be prevented.